Data rate profiles of coded/uncoded power line channel with single-carrier/multicarrier modulation techniques - Adebisi, Samuel; Oyetunji, Samson A. (Electrical, Control and Communication Engineering, 2018)
The power-line communication (PLC) technique involves sending information through an electrical conductor for a commercial or domestic purpose. Lately, electronic means of communication have gained popularity for the transfer of information. Conversely, there is an increased requirement for more transmission media, like the use of power line as a communication channel for remote data delivery. This paper focuses on determining the data rate profile achievable using the single-carrier/multicarrier modulation techniques with Reed- Solomon concatenated convolutional (RS-CC) codes for data transmission through a power line channel. In this investigation, MATLAB/SIMULINK was used to explore a low-voltage power line as a communication channel for high data transmission rate. Data transmission was accomplished by utilizing a parametric model of a power line channel with the different kinds of noise considered in the simulation. In the designed power-line communication (PLC) system, single-carrier modulation offered a maximum of 14.4 Mbps reduction in the data rate when the uncoded 64-quadrature amplitude modulation (QAM) was compared to coded 64-QAM with 1/2 forward error correction (FEC). In the OFDM power-line communication (PLC) system, the decrease in the data rate was maximal at 39 Mbps when the uncoded 16-QAM was contrasted with the 16-QAM having 1/2 FEC. It was evident that the increased code rate of the PLC system using single-carrier and OFDM modulation implied increased data rate profiles